A tailored approach to BRAF and MLH1 methylation testing in a universal screening program for Lynch syndrome - Adar, Tomer; Rodgers, Linda H; Shannon, Kristen M; Yoshida, Makoto; Ma, Tianle; Mattia, Anthony; Lauwers, Gregory Y; Iafrate, Anthony J; Chung, Daniel C (Modern pathology, 2017)
To determine the correlation between BRAF genotype and MLH1 promoter methylation in a screening program for Lynch syndrome (LS), a universal screening program for LS was established in two medical centers. Tumors with abnormal MLH1 staining were evaluated for both BRAF V600E genotype and MLH1 promoter methylation. Tumors positive for both were considered sporadic, and genetic testing was recommended for all others. A total 1011 colorectal cancer cases were screened for Lynch syndrome, and 148 (14.6%) exhibited absent MLH1 immunostaining. Both BRAF and MLH1 methylation testing were completed in 126 cases. Concordant results (both positive or both negative) were obtained in 86 (68.3%) and 16 (12.7%) cases, respectively, with 81% concordance overall. The positive and negative predictive values for a BRAF mutation in predicting MLH1 promoter methylation were 98.9% and 41%, respectively, and the negative predictive value fell to 15% in patients ≥70 years old. Using BRAF genotyping as a sole test to evaluate cases with absent MLH1 staining would have increased referral rates for genetic testing by 2.3-fold compared with MLH1 methylation testing alone (31% vs 13.5%, respectively, P <0.01). However, a hybrid approach that reserves MLH1 methylation testing for BRAF wild-type cases only would significantly decrease the number of methylation assays performed and reduce the referral rate for genetic testing to 12.7%. A BRAF mutation has an excellent positive predictive value but poor negative predictive value in predicting MLH1 promoter methylation. A hybrid use of these tests may reduce the number of low-risk patients referred to genetic counseling and facilitate wider implementation of Lynch syndrome screening programs.